Rape culture, lad culture and everyday sexism: researching, conceptualizing and politicizing new mediations of gender and sexual violence - Phipps, Alison; Ringrose, Jessica; Renold, Emma; Jackson, Carolyn (Journal of gender studies, 2018)
Introduces a special journal issue devoted to the subject.